Optimizing School Operational Support Fund Management to Support Teacher Performance Improvement: Optimalisasi Pengelolaan Dana Bantuan Operasional Sekolah untuk Mendukung Peningkatan Kinerja Guru - Elfrida Sinambela; Ali Idrus; Mayasari Mayasari (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education quality is closely linked to how financial resources are managed, particularly in public schools. Specific Background: BOS (School Operational Assistance) funds are crucial in Indonesia's educational framework, yet their effectiveness in improving teacher performance remains underexplored at the micro level. Knowledge Gap: Few studies have examined how structured fund management influences teacher performance through school-based planning and implementation. Aims: This study aims to analyze the management of BOS funds at SMP N 62 Muaro Jambi, focusing on four administrative aspects—planning, organizing, implementation, and evaluation—and how these influence teacher performance. Results: Using a qualitative descriptive approach with inductive analysis, findings indicate that BOS fund management follows a systematic process led by a designated team. Effective allocation supports teacher development through improved facilities and professional training. Novelty: The study highlights the role of strategic planning and stakeholder coordination in maximizing limited resources while addressing challenges like delayed disbursement. Implications: Strengthening internal coordination and improving fund disbursement mechanisms can significantly enhance educational outcomes by empowering teachers, suggesting that governance reforms at the school level may yield broader systemic benefits. Highlights: Structured Management: BOS funds are managed through planning, organizing, implementation, and evaluation. Performance Impact: Effective fund use enhances teacher performance via training and facilities. Challenge & Solution: Delays and limited funds are tackled through improved coordination and planning. Keywords: BOS Fund Management, Teacher Performance, Educational Quality, School Governance, Resource Allocation